Peran Social Media Specialist dalam Meningkatkan Kesadaran Peduli Sampah Melalui Instagram @synergynara - Peragi, Aldi; Putri, Wirda Yulita (Universitas Pahlawan Tuanku Tambusai, 2025)
Technology has greatly influenced how people communicate and has led to the creation of new professions, such as Social Media Specialists, who play an essential role in connecting organizations with audiences. One example is Nara Synergy, an organization that uses Instagram to actively promote environmental issues, particularly focusing on waste awareness. In Indonesia, waste remains a significant concern, with data showing that approximately 72% of the public lacks sufficient awareness of the issue.This study aims to understand how a Social Media Specialist can utilize Instagram, specifically through @synergynara, to boost waste awareness. The research objective is to examine